(untitled) (Research, Society and Development, 2021)
This study aimed to analyse the safety and efficacy of bacterial cellulose (CB) produced from sugarcane molasses, through studies conducted and published by the Sugarcane Biopolymers Research Group, POLISA©, Biopolymers for Health. This is a narrative review of the literature that was conducted from the collection of publications on sugarcane biopolymers, linked to POLISA©, Biopolymers for Health researchers. Twenty one studies published between the years 2002 to 2020 were selected, of which 11 studies related to pre-clinical evaluation and 10 to clinical evaluation. Studies involving toxicological and biocompatibility assessments described the safety and risks related to the use of CB, while those of clinical evaluation investigated the healing process and tissue remodelling, and estimated its effectiveness as a dressing. In conclusion, CB did not prove to be cytotoxic, genotoxic or acutely toxic, showing high biocompatibility, in addition, it proved to be effective in inducing the healing process and tissue remodeling.